Importância de polimorfismos dos genes CFH, LOC387715 e VEGF na resposta terapêutica da degeneração macular relacionada à idade exsudativa aos antiangiogênicos - Carlos Eduardo dos Reis Veloso (2012)
PURPOSE: To investigate the role of CFH, LOC387715 and VEGF genepolymorphisms on the outcome of antiangiogenic treatment for neovascular agerelated macular degeneration (AMD) with bevacizumab and ranibizumab. METHOD: Best-corrected visual acuity (VA) and central macular thickness (CMT) were measured before and one, three and six months after bevacizumab or ranibizumab loading dose (three consecutive injections with 1 month interval) had been initiated. The patients were genotyped for three single nucleotide polymorphisms: rs1061170 in the CFH gene, rs10490924 in the LOC387715 gene and rs1413711 in the VEGF gene. RESULTS: A total of 95 eyes of 95 patients were included in the study. For the CFH rs1061170 and LOC387715 rs10490924 polymorphisms, when the mean improvement of VA and CMT was compared between the different genotypes, no statistically significant difference was noted in any of the visits. For both genes, therewas no difference when a VA improvement three lines was evaluated (p>0,05). For the VEGF rs1413711 polymorphism, patients homozygous for the risk allele showed, at the first and third month, greater mean VA improvement than the others (p<0.05). A VA improvement three lines at the first month was also greater for this group of patients (p=0,005). There was no difference when the mean CMT improvement was compared between the VEGF genotypes (p<0,05). For the three studied genes, there was no statistically significant difference when the mean number of intravitreal injections required was evaluated. CONCLUSION: For the CFH rs1061170 and LOC387715 rs10490924 polymorphisms, there was no difference in response between genotypes. For the VEGF rs1413711 polymorphism, patients homozygous for the risk allele showed better response to anti-VEGF therapy for neovascular AMD.